Intelligent Science and Intelligent Data Engineering Third Sino-foreign-interchange Workshop, IScIDE 2012, Nanjing, China, October 15-17, 2012, Revised Selected Papers - Yang, Jian; Fang, Fang; Sun, Changyin (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2013)
This book constitutes the proceedings of the third Sino-foreign-interchange Workshop on Intelligence Science and Intelligent Data Engineering, IScIDE 2012, held in Nanjing, China, in October 2012. The 105 papers presented were carefully peer-reviewed and selected from 429 submissions. Topics covered include pattern recognition; computer vision and image processing; machine learning and computational intelligence; knowledge discovery, data mining, and web mining; graphics and computer visualization; and multimedia processing and applications.